Political Marketing Communication Strategies of LHKP Muhammadiyah East Java for the 2024 Legislative Elections - Ananta, Yogaraksa; Suwarko, Andi (Indonesian Journal of Political Studies, 2026)
This study examines how the Institute of Public Policy and Wisdom (LHKP) of the East Java Muhammadiyah Regional Board employs political communication strategies to support its candidates in the 2024 Legislative Election. Using a qualitative descriptive approach, it investigates the institutional mechanisms and their influence on candidates and voters. The findings reveal that LHKP East Java implemented a structured communication system that included forming dedicated winning teams, strengthening inter-regional networks, and strategically using internal and social media platforms. Moreover, political messages were crafted around the religious concept of amar ma'ruf nahi munkar to resonate with the organization’s ideological identity. Nonetheless, these strategies were not executed optimally. While the "Jipolmu" constituency produced cognitive, affective, and conative effects, the overall impact was limited by the narrow scope of grassroots outreach. These results underscore the difficulties faced by religious civil society organizations in a competitive electoral landscape.